PENGARUH KUALITAS PELAYANAN TERHADAP KEPERCAYAAN PESERTA PBPU BPJS KESEHATAN PADA BPJS KESEHATAN CABANG PADANG DI KOTA PADANG - Yossi Lusiana; Aldri Frinaldi; Nora Eka Putri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
The puspose of this research is to examine the influence between the quality of service towards trust of participants of BPJS Health Care in Padang which in class of Workers Not Wage Receivers or Independent Workers. The type of research is assosiative. Population in this research are amounted to 155.669 people. The sampling technique is accidental sampling. Sample in this research are amounted to 398 people. Data collecting using a questionnaire based on a Likert scale that has been tested for validity and reliability. The results showed the public’s assessment of the quality of BPJS Health Care participant services and trust in Padang rated high (74.78% and 72.60%). There is significant influence between tangible and trust with 0.004 significant value. These hyphoteses were tested by using Model Summary and the Ajusted R Square value of 0.57. There is no significant influence partially between reliability and trust with 0.300 significant value. There is no significant influence between responsiveness and trust on a 0.117 significant value. There is significant influence between assurance and trust with 0.000 significant value. These hyphoteses were tested by using Model Summary and the Ajusted R Square value of 0.112. There is significant influence between emphaty and trust with 0.024 significant value. These hyphoteses were tested by using Model Summary and the Ajusted R Square value of 0.88. There are significant influence simultaneously between tangible, reliability, responsiveness, assurance, emphaty variables and trust on 0.000 significant value and the Ajusted R Square value of 0.168 that means the contribution quality of service to trust is 16.8%.